The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1046/j.1365-313x.2003.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Repression of gene expression by Arabidopsis HD2 histone deacetylases

Abstract: SummaryThe four HD2 proteins of Arabidopsis thaliana (AtHD2A±D) belong to a unique class of histone deacetylases that is plant speci®c. Previously, we have demonstrated that one of the members, AtHD2A, can mediate transcriptional repression when targeted to the promoter of a reporter gene. Here, we report that AtHD2B and AtHD2C can also repress gene expression. AtHD2A and AtHD2C differ from AtHD2B and AtHD2D in the composition of their structural domains. Our data show that both structural types play a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 38 publications
2
73
0
Order By: Relevance
“…Therefore, the most straightforward interpretation of these results is that the elevated expression levels of the CPC and GL2 genes are directly affected by histone hyperacetylation. The down-regulation of WER gene expression hyperacetylation does not fit this pattern, but there are a number of cases where histone hyperacetylation decreases gene expression (29)(30)(31). As expected based on the microarray and semiquantitative RT-PCR results, no discernable changes in the PCR products of the TTG promoters were observed after TSA treatment, although a slight increase in the upstream region of acetylated H4 was detected (Fig.…”
Section: Tsa Treatment Alters Cellular Pattern By Changing the Expressupporting
confidence: 50%
“…Therefore, the most straightforward interpretation of these results is that the elevated expression levels of the CPC and GL2 genes are directly affected by histone hyperacetylation. The down-regulation of WER gene expression hyperacetylation does not fit this pattern, but there are a number of cases where histone hyperacetylation decreases gene expression (29)(30)(31). As expected based on the microarray and semiquantitative RT-PCR results, no discernable changes in the PCR products of the TTG promoters were observed after TSA treatment, although a slight increase in the upstream region of acetylated H4 was detected (Fig.…”
Section: Tsa Treatment Alters Cellular Pattern By Changing the Expressupporting
confidence: 50%
“…Histone deacetylases and methylases control rDNA genes and thus regulate the epigenetic on/off switch (gene dosage), providing an important mechanism in the biogenesis of ribosomes (25,27). It has been demonstrated that the activity of the yeast RPD3 is required for nucleolar reorganization and RNA pol I delocalization via its association with the rDNA chromatin, which can be antagonized by TOR (13).…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome contains four isoforms of the HDT-type histone deacetylases, namely AtHD2A, AtHD2B, AtHD2C, and AtHD2D, among which AtHD2A and AtHD2B share the highest sequence homology and the apparent functional similarities (27)(28)(29). To test the specificity of interaction between RPS6 and the AtHD2B, GFP fusion construct of a fulllength RPS6 (S6FL-GFP) was co-expressed with AtHD2A in protoplasts (Fig.…”
Section: Identification Of Proteins Interacting With the Rps6 Cmentioning
confidence: 99%
“…In addition, plants contain an uncommon class of HDACs, the HD2 class, which was identified in plants only (Lusser et al, 1997;Aravind and Koonin, 1998;Wu et al, 2000aWu et al, , 2003Dangl et al, 2001;Zhou et al, 2004). Studies on the mechanism of action of HDACs in plants are beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%